Network measurement - Shen, Wanxing. (2011)
In Network Measurement, network engineers are interested in how switched packets travel from the source node to its destination node. The route each packet takes to its destination address affects greatly on the speed of the internet. Although trace route has been widely used in the world of network weather forecasting, the accuracy of the data gathered is loss due to only a single location trace. To obtain a more precise measurement, we have to obtain the measurement data from various network locations. However, most of the measurement websites out there either do not provide a graphical trace route solution or the trace route parameters are too few for network engineers to use.